Jacks of metal/metalloid chelation trade in plants—an overview - Anjum, Naser A.; Hasanuzzaman, Mirza; Hossain, Mohammad A.; Thangavel, Palaniswamy; Roychoudhury, Aryadeep; Gill, Sarvajeet S.; Rodrigo, Miguel A. Merlos; Adam, Vojtěch; Fujita, Masayuki; Kizek, Rene; Duarte, Armando C.; Pereira, Eduarda; et al. (Frontiers in Plant Science, 2015)
Varied environmental compartments including soils are being contaminated by a myriad toxic metal(loid)s (hereafter termed as ‘metal/s’) mainly through anthropogenic activities. These metals may contaminate food chain and bring irreparable consequences in human. Plant-based approach (phytoremediation) stands second to none among bioremediation technologies meant for sustainable cleanup of soils/sites with metal-contamination. In turn, the capacity of plants to tolerate potential consequences caused by the extracted/accumulated metals decides the effectiveness and success of phytoremediation system. Chelation is among the potential mechanisms that largely govern metal-tolerance in plant cells by maintaining low concentrations of free metals in cytoplasm. Metal-chelation can be performed by compounds of glutathione (GSH) (reduced GSH; phytochelatins, PCs; metallothioneins, MTs) and non-GSH (histidine, nicotianamine, organic acids) origin. This paper presents an appraisal of recent reports on both GSH and non-GSH associated compounds in an effort to shed light on the significance of these compounds in metal-plant tolerance, as well as to provide scientific clues for the development of phytoextraction strategies.